До історії скансенів у Європі - Башкатов, Ю.Ю.; Терпиловський, Р.В. (Археологія і давня історія України, 2011)
У статті подано історію становлення та розвитку скансенів у Європі. На основі досвіду створення таких музеїв розглянуто можливість створення скансена на півострові Барбара. Статья посвящена истории скансенов в Европе, насчитывающей уже 120 лет. Рассмотрена как история развития идей по созданию музеев под открытым небом, так и отдельных комплексов (их экспонатов, развитию). Отдельно освещены вопросы реконструкций по археологическим данным. Также в статье кратко описаны основные скансены Украины, современное развитие данной идеи в нашей стране и возможности создания археопарка в г. Комсомольск Полтавской области. The article is sanctified to history of scansens in Europe, already counting 120 years. Both history of development of ideas is considered on creation of museums under open-skies and separate complexes (their exhibits, development). The questions of reconstructions from archaeological data are separately lighted up. Also in the article the basic are briefly described scansens Ukraine, modern development of this idea in our country and possibility of creation of archaeopark in Komsomol`sk of the Poltava region.